2018
DOI: 10.1161/jaha.118.008854
|View full text |Cite
|
Sign up to set email alerts
|

Postural Hyperventilation as a Cause of Postural Tachycardia Syndrome: Increased Systemic Vascular Resistance and Decreased Cardiac Output When Upright in All Postural Tachycardia Syndrome Variants

Abstract: BackgroundPostural tachycardia syndrome (POTS) is a heterogeneous condition. We stratified patients previously evaluated for POTS on the basis of supine resting cardiac output (CO) or with the complaint of platypnea or “shortness of breath” during orthostasis. We hypothesize that postural hyperventilation is one cause of POTS and that hyperventilation‐associated POTS occurs when initial reduction in CO is sufficiently large. We also propose that circulatory abnormalities normalize with restoration of CO 2.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…Third, a large number of studies using transcranial Doppler have shown that cerebral blood flow velocity is influenced by P ET CO 2 ( Del Pozzi et al, 2014 , Immink et al, 2014 , Laffey and Kavanagh, 2002 , Novak et al, 1998 , Sato et al, 2012 , Stewart et al, 2018a , Stewart et al, 2018b ). Using extracranial Doppler, this finding was also confirmed in our previous study ( van Campen et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a large number of studies using transcranial Doppler have shown that cerebral blood flow velocity is influenced by P ET CO 2 ( Del Pozzi et al, 2014 , Immink et al, 2014 , Laffey and Kavanagh, 2002 , Novak et al, 1998 , Sato et al, 2012 , Stewart et al, 2018a , Stewart et al, 2018b ). Using extracranial Doppler, this finding was also confirmed in our previous study ( van Campen et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 recordings are useful to detail the pathophysiological cascade as hypocapnia may precede reflex syncope (Norcliffe-Kaufmann et al, 2008). Adding CO 2 recordings to TTT may also be of clinical interest as it may help to identify POTS subtypes that are consequent upon postural hyperventilation (Stewart et al, 2018) or episodes of hyperventilation in those who report dizziness without concomitant hypotension (Naschitz et al, 2000).…”
Section: Respiratory Recordingsmentioning
confidence: 99%
“…Other causes of TLOC, including epilepsy, metabolic disorders (such as hypoglycemia, hypoxemia, hyperventilation syndrome [10]), poisoning, transient ischemic attack of the vertebral basilar artery system, ''pseudo-syncope" caused by psychological factors [6,11] and TLOC from head trauma are easily misdiagnosed as syncope in the clinic. These diseases do not produce transient cerebral ischemia, so they should be strictly differentiated from syncope (Ⅱa; A).…”
Section: The Underlying Diseases Of Syncope In Children and Adolescentsmentioning
confidence: 99%